1954
DOI: 10.1099/00221287-11-3-364
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Segregation and the Growth of Clones of Spontaneous Mutants of Bacteria

Abstract: SUMMARY: An investigation of the rate of increase of spontaneous mutants and the subsequent increase in mutant proportion in a bacterial culture revealed discrepancies between the observed results and those expected on the assumption that mutant and parent grew with equal rates. These discrepancies could not be accounted for in terms of a selective difference between established mutants and their parents since, when the two were mixed together in reconstruction experiments, they fared equally well for hundreds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

1957
1957
2005
2005

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 14 publications
1
23
1
Order By: Relevance
“…The nuclei were usually easy to count in all organisms in contrast to the preparations reported previously (Ryan & Wainwright, 1954). The average number of nuclei was 1.8 with an insignificant variation from 1.5 to 2-1, irrespective of stage or temperature.…”
Section: Resultscontrasting
confidence: 40%
See 2 more Smart Citations
“…The nuclei were usually easy to count in all organisms in contrast to the preparations reported previously (Ryan & Wainwright, 1954). The average number of nuclei was 1.8 with an insignificant variation from 1.5 to 2-1, irrespective of stage or temperature.…”
Section: Resultscontrasting
confidence: 40%
“…The exponential results obtained indicated that there was a selection for the hf bacteria at 1 5 ' , a phenomenon not observed at 3 7 ' . The initial slope of the increase curve was, however, c. 9 x 10-9 which when compared with the value of 7 x found in the Poisson experiments, suggested the presence of 8 instead of 4 mutable units as had been found at 37' by the same scheme of comparison (Ryan & Wainwright, 1954). Therefore, when the mutation rates at other temperatures were divided by 4 and that at 15O by 8, indistinguishable mutation rates/ mutable unit/generation are obtained.…”
Section: Methodsmentioning
confidence: 72%
See 1 more Smart Citation
“…Yet proflavin, which induces auxotrophs, also does not revert the his-gene. Moreover, the possibility has not been excluded that the mutable unit under investigation is composed of RNA or protein even though it is located in a DNA-containing body (Ryan & Wainwright, 1954). Not enough evidence is as yet at hand to require rejection of the proposition that some natural mutations may result from copy-errors during the replication of the gene.…”
Section: Discussi~nmentioning
confidence: 99%
“…In microbial organisms, the rate of mutation can be measured by Luria-Delbrück fluctuation analysis (1) or in continuous cultures (2,3). By such methods, the rates of inactivating ( forward) mutations in lacI in Escherichia coli and CAN1 in Saccharomyces cerevisiae have been estimated to be 4 Â 10 À7 and 1 Â 10 À7 , respectively (4,5).…”
Section: Introductionmentioning
confidence: 99%